Analisis Pemungutan Retribusi Tempat Penginapan Oleh Dinas Pariwisata Kabupaten Poso - RUMANDJO, YELSTI WELNIATI; Elim, Inggriani; Wangkar, Anneke (Universitas Sam Ratulangi, 2024)
Lodging levies are levies imposed on the use or usage and services of lodging provided, owned and managed by the Regional Government. This research aims to determine the collection of lodging levies by the Poso Regency Tourism Office in increasing Poso Regency’s Original Regional Income. The analytical method used in this thesis research is a descriptive analysis method which aims to describe, compare, provide an overview of agencies and explain data so as to produce a conclusion in accordance with the data collected and the type of research used is descriptive qualitative. The research results show that the collection of accommodation levies by the Poso Regency Tourism Office based on Regional Regulation Number 3 of 2021 Article 41 Paragraph 1, 2, 3, and 4 is in accordance with existing regional regulations. The decrease in the realization of lodging levy receipts has nothing to do with the procedures for collecting it, the decrease is cause by several external factors.